RESPON TERHADAP MAJELIS AGAMA BUDDHA TENTRAYANA SATYA BUDDHA INDONESIA DI KALIMANTAN BARAT - Nuhrison M. Nuh (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
There are many sects of Buddhism , some of them are Theravada or Hinayana, Satya Buddhism and Tantrayana Zhenfo Zhong. The last one, is developed by Lu Sheng in Seattle, USA. The difference of this school with other Buddhism teachings is the life of Buddha, teacher`s cult, Bhiksu and Bhiksuni can marry and glamorious life of its tearcher. The live Buddha is known with his teachings that people are enlightened and still life. Those followers of Tantrayana which is known as live Buddha is Lu Sheng Yen himself as Maha Mula Vajra Acharya. This research is done by qualitative approach.